3D simulation on 90 degree off-take branching channel with separation zones - Zakaria, Siti Aimi Asyarah (2023)
Flow separation occurs often in river diversion, particularly in branch channels. The flow separation is generally seen through its separation area, which is influenced by a number of factors such as off-take angles, discharge ratios, and channel widths. The study was conducted through computational modelling of FLOW-3D to create a relationship between discharge ratio with the size of the separation area. The model domain was setup with a channel bifurcating into two, the main channel downstream and a channel representing the river diversion at a 90°. The model was first validated with previous laboratory work. Then, three discharge ratios were simulated, which are 0.21, 0.49 and 0.70. The layers within the depth of the water were also investigated to understand whether the separation area is homogenous within the water depth via the vertical confinement product. The length of separation area was observed for a few layers within the water depth. The results shows that the separation area is homogenous within the water depth and a single depth can be applied to represent the whole channel. As for the separation area, the result shows a good agreement with previous work. The length of separation zone decreases as discharge ratio increases.